Two Decades of Evolution of Our Understanding of the Transient Receptor Potential Melastatin 2 (TRPM2) Cation Channel - Szollosi, Andras (Life (Basel), 2021)
The transient receptor potential melastatin (TRPM) family belongs to the superfamily of TRP ion channels. It consists of eight family members that are involved in a plethora of cellular functions. TRPM2 is a homotetrameric Ca(2+)-permeable cation channel activated upon oxidative stress and is important, among others, for body heat control, immune cell activation and insulin secretion. Invertebrate TRPM2 proteins are channel enzymes; they hydrolyze the activating ligand, ADP-ribose, which is likely important for functional regulation. Since its cloning in 1998, the understanding of the biophysical properties of the channel has greatly advanced due to a vast number of structure–function studies. The physiological regulators of the channel have been identified and characterized in cell-free systems. In the wake of the recent structural biochemistry revolution, several TRPM2 cryo-EM structures have been published. These structures have helped to understand the general features of the channel, but at the same time have revealed unexplained mechanistic differences among channel orthologues. The present review aims at depicting the major research lines in TRPM2 structure-function. It discusses biophysical properties of the pore and the mode of action of direct channel effectors, and interprets these functional properties on the basis of recent three-dimensional structural models.